The Cimarron Volunteer Fire Dept. Basketball tournament! (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement for The Cimarron Volunteer Fire Dept. in Cimarron, New Mexico.
Master List item # 21
File location is in the Raton File Cabinet
Keywords: Carter, Eddie; Archuleta, Larry; Cimarron Fire Department; Cimarron High School Gym; Fire Department; Basketball; Ladies' Auxiliary; Cimarron, New Mexico